The Effectiveness of Inquiry and Practice During Project Design Courses at a Technology University - Fan, Jing-Yun; Ye, Jian-Hong (Frontiers in Psychology, 2022)
Project design is an important course that examines the achievements of Taiwan’s technology university students, so students are expected to optimize their creativity, critical thinking, and practical skills to demonstrate their product design and production abilities. It is therefore important for teachers to act as effective facilitators in this course and to guide students to develop their potential through appropriate teaching methods. Among the many teaching methods, inquiry-based teaching is considered to be an effective way for students to learn and solve problems on their own. However, most of the research related to inquiry-based teaching and learning has concentrated mainly on K-12 education, while few to no studies have focused on the application of inquiry-based teaching and learning in project design courses at university level. Therefore, in order to expand the understanding of the application effect of inquiry-based teaching at university level, this study adopted the quasi-experimental design method, and through the purposive sampling method, 20 students from the fashion design department at a technology university were invited to participate in this study. During the 9-month period, teaching experiments were carried out using two inquiry modules, QC/ADEAC and QD/ODEAC. First, when participants were thinking of a creative topic, they followed the process: Question (Q), Collection/Analysis (C/A), Discussion (D), Explanation (E), Amendment (A), and Confirmation (C) in the course. During the production process, the participants were allowed to improve on their work through the process of Question (Q), Doing/Observation D/O, Discussion (D), Explanation (E), Amendment (A) and Confirmation (C). The teacher became a true guide, so that the participants could explore and work out how to improve their designs through independent inquiry and practice. The results showed that the participants’ works had a good degree of completion and creative performance.